Analisis Literatur Tentang Kerangka Pengukuran Kinerja dan Akuntabilitas dalam Pengiriman Layanan Publik - Permata Pebester Natalia Hutahaean; Hamdani Dahyufi; Andriansah Andriansah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes performance measurement frameworks and accountability mechanisms in public service delivery through a comprehensive literature review of studies published between 2015 and 2025. Although models such as the 3E (economy, efficiency, effectiveness) and IOO (input–output–outcome) frameworks are widely used in public administration, evidence indicates that their implementation often falls short due to data limitations, bureaucratic resistance, and limited utilization of performance results in decision-making. The literature also highlights a persistent gap between theoretical performance frameworks and actual public service practices, particularly in capturing service quality and meaningful outcomes for citizens. Recent studies emphasize that citizen satisfaction and public perception are essential indicators that must be integrated into contemporary performance measurement systems. This study concludes that performance measurement and accountability are interdependent mechanisms that require strengthened organizational capacity, relevant indicators, and a culture of evidence-based improvement to enhance public service quality.